FACTORS AFFECTING EFL STUDENTS’ UNWILLINGNESS TO COMMUNICATE IN ENGLISH IN CAMPUS - Pakpahan, Marnangkok; ., Ikhsanudin; Sada, Clarry (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract Language learners’ willingness to communicate in the target language is the key role in achieving their language learning goals. The notion of ‘Willingness to Communicate’ (WTC) is a model or concept that integrates psychological, linguistic, and communicative variables in order to describe, explain, and predict foreign or second language communication. This study was conducted to explore the possible factors affecting EFL students’ unwillingness to communicate in English in campus. The data were gathered from three research participants using unstructured interview and were analyzed qualitatively using narrative inquiry method and thematic analysis strategy. The findings of this study revealed that the main factors affecting the students’ unwillingness to communicate in English during the learning time in campus were linguistic, psycholinguistic, socio-cultural, and institutional factors. And among those major factors, socio-cultural and institutional factors were identified to be the most dominant ones that affected the participants’ unwillingness to communicate in English in campus. Keywords: English as a Foreign Language (EFL), Narrative inquiry,                           Willingness to Communicate (WTC)   Abstrak Kemauan mahasiswa jurusan bahasa untuk menggunakan bahasa sasaran dalam berkomunikasi adalah menjadi kunci utama untuk mencapai tujuan mereka mempelajari bahasa tersebut. Konsep kemauan untuk menggunakan bahasa sasaran dalam berkomunikasi adalah merupakan sebuah model yang mengintegrasikan variabel-variabel psikologis, linguistik dan komunikatif untuk mendiskripsikan, menjelaskan dan memprediksi kemampuan berkomunikasi dalam bahasa asing. Penelitian ini bertujuan untuk mengeksplorasi faktor-faktor penyebab mahasiswa jurusan bahasa Inggris merasa enggan berbahasa Inggris dikampus. Data penelitian ini diperoleh dari tiga mahasiswa dengan menggunakan wawancara yang tidak terstruktur dan data tersebut kemudian dianalisa secara kwalitatif dengan menggunakan metode ‘narrative inquiry’ dan strategi analisis tematik. Temuan dari penelitian ini menunjukkan bahwa faktor-faktor utama yang menyebabkan mahasiswa merasa enggan untuk berkomunikasi dalam bahasa Inggris dikampus adalah faktor- faktor linguistik, psikolinguistik, sosial budaya dan institusional. Faktor sosial budaya dan faktor institusional terbukti menjadi dua faktor yang paling berpengaruh terhadap penyebab keengganan mahasiswa untuk berkomunikasi dalam bahasa Inggris dikampus. Kata kunci: Bahasa Inggris sebagai bahasa asing, Narrative inquiry, Kemauan untuk berkomunikasi Marnangkok Pakpahan, Ikhsanudin, Clarry Sada Masters Study Program of English Language Education, Teacher Training and Education Faculty, Tanjungpura University, Pontianak Email: marnangkok.pphn@gmail.com